A detailed study on void growth and crack-void interaction in plastically compressible bilinear hardening and trilinear hardening-softening-hardening solids - Pandey S.; Kumar S.; Khan D. (My University, 2025)
This paper provides detailed investigations on void growth and crack-void interaction ahead of a moving crack-tip for a mode I crack in plastically compressible solid. A finite strain elastic-viscoplastic material model with hardening-hardening and hardening-softening-hardening hardness functions is used in the finite element simulation. The plastic compressibility leads to an increased crack opening displacement. The plastic compressibility together with material softening considerably increase stress triaxiality and decrease the void and crack growth. For plastically compressible solids, void growth is more in normal direction to the crack plane and increase in initial void size is accompanied by decrease in the crack and void growth. © 2024 Taylor & Francis Group, LLC.